Kisspeptin receptor (version 2020.4) in the IUPHAR/BPS Guide to Pharmacology Database - Davenport, Anthony P.; Maguire, Janet J.; Mead, Edward J.; Pawson, Adam J. (IUPHAR/BPS Guide to Pharmacology CITE, 2020)
The kisspeptin receptor (nomenclature as agreed by the NC-IUPHAR Subcommittee on the kisspeptin receptor [9]), like neuropeptide FF (NPFF), prolactin-releasing peptide (PrP) and QRFP receptors (provisional nomenclature) responds to endogenous peptides with an arginine-phenylalanine-amide (RFamide) motif. kisspeptin-54 (KP54, originally named metastin), kisspeptin-13 (KP13) and kisspeptin-10 (KP10) are biologically-active peptides cleaved from the KISS1 (Q15726) gene product. Kisspeptins have roles in, for example, cancer metastasis, fertility/puberty regulation and glucose homeostasis.